Leflunomide Induced Toxic Epidermolysis Necrosis in Patient with Rheumatoid Arthritis - Pyakurel, Bibek; Basnet, Prava (Journal of Manmohan Memorial Institute of Health Sciences, 2025)
Leflunomide is immunomodulating agent used in rheumatoid arthritis and other rheumatic diseases like psoriatic arthritis and systemic lupus erythematous. Minor side effects of leflunomide (